The Cultural Capital of Pandalungan Coffee Farmers in Building Sustainable Food Security - Maulana, Amri Dhimas; Supriatna, Nana (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
This studi aims to explore the role of cultural capital of Pandhalungan coffee farmers in Jember Regency in their efforts to build sustainable food security. This study used a qualitative approach with a phenomenological design to explore the experiences, perceptions, and practices of coffee farmers in utilizing their cultural capital to improve economic, social, and environmental well-being at the local level. Data collection used in-depth interviews and participatory observation with a number of coffee farmers. Data analysis was conducted thematically to identify the main patterns, key findings, and perspectives that emerged from participants' narratives. The results of this studi showed that the types of cultural capital owned by Pandalungan coffee farmers include traditional knowledge, local agricultural practices, community values, and social norms that support food security. The Coffee farmers in Pandalungan have in-depth knowledge of traditional farming practices passed down through generations. This knowledge includes specific techniques in planting, tending and harvesting coffee that are adapted to local conditions. In addition, the cultural capital of Pandalungan coffee farmers plays a crucial role in supporting sustainable food security.